PERENCANAAN ARSITEKTUR ENTERPRISE MENGGUNAKAN TOGAF ADM PADA SARANA WEDDING ORGANIZER - Ariati, Nining; Maulana, Muhammad Mico; Juliansyah, M. Agung; Febrianza, M.; Setiawan, Ichan; Fahlevi, Reza; Syaharena, Syaharena (LPPM Universitas Bina Bangsa, 2024)
This study aims to design an enterprise architecture using TOGAF ADM for CV Sarana Wedding Organizer. The methodology used is qualitative with a literature study and theoretical analysis approach. Data collection was conducted through observation and interviews. The results show that the implementation of TOGAF ADM can provide structured guidance in developing integrated information systems. The research produced an architectural planning that includes the preliminary phase, architecture vision, business architecture, information systems architecture, technology architecture, and opportunities and solutions. This architectural design is expected to assist CV Sarana Wedding in digital transformation and improving its business operational efficiency.